Linkages between land management, land degradation, and poverty in Sub-Saharan Africa: The case of Uganda - Nkonya, Ephraim M.; Pender, John L.; Kaizzi, Kayuki C.; Kato, Edward; Mugarura, Samuel; Ssali, Henry; Muwonge, James (International Food Policy Research Institute, 2008)
Agriculture is vital to the economies of Sub-Saharan Africa: two-thirds of the region’s people depend on it for their livelihoods. Nevertheless, agricultural productivity in most of the region is stagnant or declining, in large part because of land degradation. Soil erosion and soil nutrient depletion degraded almost 70 percent of the region’s land between 1945 and 1990; 20 percent of total agricultural land has been severely degraded. If left unchecked, land degradation could seriously threaten the progress of economic growth and poverty reduction in Africa. Within this context, most African countries strive to achieve poverty reduction and sustainable land management. In designing policies to achieve these objectives concurrently, a clear understanding of their linkage is crucial. Nonetheless, the relationships between poverty and land management are complex, context specific, and resource specific, and empirical evidence to demonstrate their linkage has been limited. This analysis seeks to improve the understanding of this linkage by examining how poverty (broadly defined to include limited access to capital, infrastructure, and services) influences land-management practices, land degradation, crop productivity, and household incomes. In particular, the study focuses on how factors susceptible to policy initiatives—such as education, agricultural technical assistance, and credit— affect households’ land management decisions. Uganda was chosen to serve as a case study of these issues, for several reasons. Of all Sub-Saharan African nations, Uganda has some of the most severe soil nutrient depletion in Africa: about 1.2 percent of nutrient stock stored in the topsoil is depleted by farmers each year. Also, the country contains a wide variety of agroecological zones (AEZs), making it an appropriate microcosm of Sub-Saharan Africa. The Ugandan government has also been conducting ambitious poverty-reduction and conservation efforts, and a study such as this one serves to measure those efforts. Working with the Uganda Bureau of Statistics (UBOS), the authors drew on Uganda’s 2002–03 National Household Survey, as well as a specific survey conducted to collect poverty, land management, and land-degradation data at the household and plot levels.